2018
DOI: 10.1111/coa.13225
|View full text |Cite
|
Sign up to set email alerts
|

Survival differences in nasopharyngeal carcinoma among racial and ethnic minority groups in the United States: A retrospective cohort study

Abstract: There are disparities in nasopharyngeal carcinoma survival among racial and ethnic minority groups in the United States, with American Indians/Alaskan Natives faring worst. It is critical that future research focuses on nasopharyngeal carcinoma among this population to improve survivorship and mitigate cancer-related health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
3
15
0
1
Order By: Relevance
“…Similar to previous studies [ 9 ], tumor stage was considered an important predictor of survival ( P <0.0001), and advanced tumor stage was correlated with decreased survival, particularly in patients with stage IVC who have a significantly lower survival time due to distal metastasis. Nasopharyngeal carcinoma is highly sensitive to ionizing radiation, and radiation is the main treatment for nonmetastatic diseases [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to previous studies [ 9 ], tumor stage was considered an important predictor of survival ( P <0.0001), and advanced tumor stage was correlated with decreased survival, particularly in patients with stage IVC who have a significantly lower survival time due to distal metastasis. Nasopharyngeal carcinoma is highly sensitive to ionizing radiation, and radiation is the main treatment for nonmetastatic diseases [ 10 ].…”
Section: Discussionsupporting
confidence: 81%
“…Unlike the study of Nakanishi et al [ 13 ], our results showed that chemotherapy had no impact on prognosis. Whether chemotherapy is effective for lymphoepithelial carcinoma remains controversial [ 9 , 14 ]. Therefore, large randomized clinical trials must be performed to validate our study finding.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple masses at the primary site imply that the tumor cells are active and more prone to metastasize, which bring a poor prognosis for patients. Previous studies of patients with NPC in the SEER database showed that the race [17,18], marital status [19], and age [20,21] were associated with the prognosis of the patients. However, this is based on patients who have not had distant metastases.…”
Section: Discussionmentioning
confidence: 96%
“…In a retrospective cohort study by Challapalli and colleagues, Asian/Pacific patients had the highest NPC incidence rate, but they also had the highest 5-year CSS rate, while American Indian/Alaska Native had the lowest survival [17]. Lee and Ko analyzed epidemiologic patterns and survival rates for NPC patients using the SEER statistical program and found that poor survival was associated with older age, male sex, and KSCC histology [18].…”
Section: Discussionmentioning
confidence: 99%